The Implementation Of Active Giving Questions and Getting Answer Strategy In Direct Instruction Learning Model To Improve Biology Learning Outcomes Class XI IPA 3 SMA Negeri 5 Kendari - Mauludin Hamid (Journal of Biological Science and Education, 2019)
This class action research aims to improve the learning outcomes of biology students of Class XI IPA 3 SMA Negeri 5 Kendari through learning active strategy giving questions and getting answers in the direct instruction learning model. The subjects of this study were all students registered in the even semester of the 2013/2014 academic year class XI IPA 3 SMA Negeri 5 Kendari with a total of 42 students, consisting of 11 male students and 31 female students. The initial data collection technique was done by interview and observation. The source of data from the study is the measurement of student learning outcomes tests using learning outcomes indicators according to Anderson and Krathwoll in cycle I, cycle II, and cycle III. The data obtained were analyzed using descriptive data. The results of this study concluded that the average learning achievement of students in the first cycle was 68.55%, the second cycle was 61.695 and in the third cycle was 81.81%.  Keywords: Giving Questions and Getting Answer, Direct Instruction, Learning Outcome